ASSYMETRIC PRICE TRANSMISSION IN THE PORK MEAT MARKET: EMPIRICAL EVIDENCE - Castro, Aline Carvalho de; Silva Neto, Waldemiro Alcantara da; Ribeiro, Viviane Pires (Revista Econômica do Nordeste, 2022)
The aim of this paper was to evaluate the transmission of prices, in relation to asymmetry, between the producer, wholesale and retail levels of the most relevant pork meat consumption market in Brazil, the state of São Paulo. In order to attain the proposed objective, the Asymmetric Error Correction Model (ECM) was used. The importance of this subject is due to the relevance of the domestic pork meat market given the increase in production and the subsequent generation of employment and income, and in the unprecedented application of said model on this sector in the country. Results show that the transmission of prices in the São Paulo pork meat market takes place in an symmetric manner, indicating market efficiency in relation to the transmission of prices.